The acute effect of attentional focus on tennis serve performance among Kelantan States athletes / Abdul Alif Ahlami Choohaimi - Choohaimi, Abdul Alif Ahlami (Faculty of Sports Science and Recreation, 2018)
The purpose of this was to determine the acute effect of attentional focus on tennis serve performance amongst Kelantan state athletes in one week's intervention. This study used purposive sampling where all the subjects for this study were from Kelantan Tennis State Athletes. Total of eighteen subjects participated as follow: (Age: 13.72 ± 2.19, Gender: 1.56 ± 0.51, BMI: 1.61± 0.77) subjects where 18 subject from various school in Kelantan. All the subjects were randomly divided into three groups, the internal focus group (n = 6), the external focus group (n = 6) and the control group (n = 6). In acquisition test all subjects were given 5 blocks of 5 trials for familiarization of serve skill. After finish every block of trial the received five attentional instruction depending on their group either external focus or internal focus while control group was not given any instruction they can use any internal or external instruction while execute the serve skill. Result indicated that external focus group was the highest significant of p <0.05 = 0.03 compared to internal focus and control group in serving scoring. As conclusion, the findings in this study indicated that the external focus group was shows significant improvement compared to other group in tennis serving scoring during the retention test.